Epistemic Communities in International Adjudication (2020)
Epistemic community is a descriptive and analytical category used in social sciences as a whole to denote a group of technicians or professionals sharing common constructed sensibilities. The concept has proved very popular across disciplines and has been constantly transposed across fields. As a result, it has not been univocally understood and its contours have continuously taken the particular shapes of the discipline to which it has been transposed.